2007
DOI: 10.1161/01.str.0000254475.43533.dd
|View full text |Cite
|
Sign up to set email alerts
|

The Thr715Pro Polymorphism of the P-Selectin Gene Is Not Associated With Ischemic Stroke Risk

Abstract: Background and Purpose-A ThrϾPro polymorphism at codon 715 in the coding region of the P-selectin gene has recently been described. Individuals carrying the Pro715 allele were reported to have a reduced risk of myocardial infarction. A possible association of this polymorphism with the risk of ischemic stroke is currently under discussion. Methods-We investigated the prevalence of the 715 ThrϾPro polymorphism in 450 patients aged younger than 60 years with ischemic stroke or transient ischemic attack and in 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
(10 reference statements)
2
9
1
Order By: Relevance
“…These findings confirmed the results of Barbaux et al [38]. Recently, several authors have investigation of Thr715Pro P-selectin gene polymorphism and ischemic stroke [14][15][16], they have demonstrated that there was no apparent relationship of the P-selectin Thr715Pro polymorphism with the risk of ischemic stroke. However, in the current study, we found that P-selectin Thr715Pro did not show any polymorphism in either patients or controls.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings confirmed the results of Barbaux et al [38]. Recently, several authors have investigation of Thr715Pro P-selectin gene polymorphism and ischemic stroke [14][15][16], they have demonstrated that there was no apparent relationship of the P-selectin Thr715Pro polymorphism with the risk of ischemic stroke. However, in the current study, we found that P-selectin Thr715Pro did not show any polymorphism in either patients or controls.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, the frequencies of the -2,123 C, -1,969 G and -1,817 T alleles among the control subjects were 0.338, 0.843 and 0.666, respectively, but the frequencies [19,22]. In addition, the frequencies of the 715 Pro allele among the control subjects in populations of UK, France, Germany and Austria were 0.104, 0.102, 0.139 and 0.102, respectively [16,19,22,23]. However, P-selectin Thr715Pro did not show any polymorphism in either patients or controls in this study, suggesting that the distribution of P-selectin gene frequencies might vary among the different ethnic groups.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…But the frequencies were different from those of Northern Ireland and French populations in an ECTIM study (0.386; 0.470, respectively) [11]. The frequencies of the Pro715 allele among the healthy subjects in Europeans and European-Americans were about 10% [11,14], meanwhile the Pro715 variant allele of P-selectin was found to correlate with lower sPs levels and was reported that plays a protective role of myocardial infarction in European Caucasians [15]. P-selectin polymorphisms at positions À2123C/G, À1969A/G, À1817T/C and Ser290Asn were reported to be in tight linkage disequilibrium with each other in Europeans [16].…”
Section: Discussionmentioning
confidence: 71%
“…The frequencies of the Pro715 allele among the healthy subjects in Europeans and European-Americans were about 10% (Ferrari et al, 2007;Herrmann et al, 1998), meanwhile the Pro715 variant allele of P-selectin was found to correlate with lower sPselectin levels and was reported to have a protective effect from myocardial infarction in European Caucasians (Kee et al, 2000). Among African-Americans, Val599Leu was more strongly associated with a high level of sP-selectin, and T allele frequency (0.54) was much higher than that in European-Americans (0.12).…”
Section: Discussionmentioning
confidence: 95%